Detecting and combating fake news on web 2.0 technology in the 2019 political season Indonesia - Samuel Anderson; Hapsari Dwiningtyas Sulistyani (Journal of Social Studies (JSS), 2020)
The digital age has come with lots of misinformation on the internet (web 2.0). The difference between real and fake news is unclear. This paper therefore scientifically employs algorithms and the evolution tree to help in the detection of fake news. Social bots in the spread of fake news are also detected by BotOrNot.  The research employs an in-depth qualitative but informal interview with 102 participants who are internet and social media-active as well as prospective Indonesian electorates to investigate the spread and believe in fake news. The result indicates that about 91 of the informants experience the spread of fake news on daily basis, out of which 67 succumb to the truthfulness of the news. This article therefore develops a trend of battling fake news with the application of the Inoculation theory and citizen journalism as tools to eradicate fake news that may emerge before and during the 2019 election.  ‘Ohmynews’ and ‘ABC blogs’ in the South Korean 2002 general elections and the Australian 2007 Federal elections respectively will be used as models of citizen journalism to deal with fake news that may trend on the Web 2.0 (where social media application are enabled) in the 2019 Indonesian polls.